ANALISIS PENGELOLAAN ZAKAT PADA MASA UMAR BIN KHATTAB DAN RELEVANSINYA DENGAN BAZNAS - Hidayat , Taufik; Sumengkar, Apung; Sasongko , Aryo (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2025)
This study aims to analyze the zakat management system during the reign of Caliph Umar ibn Khattab and examine its relevance to the zakat management practices implemented by the National Zakat Agency (BAZNAS) in Indonesia. The research method used was descriptive qualitative, using a library research approach, reviewing primary and secondary sources related to zakat management during the Caliphate era and contemporary zakat regulations. The results show that Umar ibn Khattab implemented a structured, transparent, and social welfare-oriented zakat management system, including systematic data collection of mustahik and muzakki (recipients of zakat), distribution of zakat according to need, and strict supervision of zakat collectors. These values ​​are strongly relevant to the zakat governance principles implemented by BAZNAS today, particularly in terms of transparency, accountability, and the utilization of zakat for the economic empowerment of the community. By adopting the spirit and policies of Umar ibn Khattab's zakat, BAZNAS can strengthen its strategic role in building social justice and reducing economic disparities in Indonesia.